THE FILM INDUSTRY AND ITS CRITICAL REFLECTIONS IN BIOGRAPHICAL DRAMAS - Rusñáková, Lenka; Kvetanová, Zuzana (Communication Today, 2025)
The film genre called biographical drama (abbreviated as biopic) focuses on depicting the unique fates and professional achievements or failures of public figures, including popular figures in the music industry. Given the long-term success of these film narratives, there is a need to explore biographical audiovisual narratives about musicians of the past and present. The main aim of the study, therefore, is to elucidate the conventional genre patterns and iconography of the film genre of biographical drama in the form of a critical reflection on feature films, contemporary biopics from the music industry that resonate in the world of cinema. To fulfil the stated aim, the first step is to explain key concepts and processes closely related to the issue at hand. In a follow-up case study, we explain the ways in which the music industry collaborates with the film industry in the application of qualitative content (narrative) analysis of selected research materials. We work on the assumption that biographical dramas about music personalities have the potential to create financially and audience successful media content, reaching relatively high qualitative levels, despite their generally low reputation by the professional public. This assumption opens up a debate about ways of working with the relevant genre iconography. We are also interested in answering the question of how and whether the meaning of the presented facts changes to dramatize the plot, and 10 what extent the examined film narratives referring to real life stories of selected persons fulfil their informative-educational character. In fact, we believe that the representation of reality in the media reality (represented by audiovisual images of the described genre) is modified to a certain extent. For this reason, we consider it necessary to approach the interpretation of cinematic works in a critical manner.